Is the Implicit Association Test a Valid and Valuable Measure of Implicit Consumer Social Cognition? - Brunel, Frédéric F.; Tietje, Brian C.; Greenwald, Anthony G. (Journal of Consumer Psychology, 2004)
This article discusses the need for more satisfactory implicit measures in consumer psychology and assesses the theoretical foundations, validity, and value of the Implicit Association Test (IAT) as a measure of implicit consumer social cognition. Study 1 demonstrates the IAT's sensitivity to explicit individual differences in brand attitudes, ownership, and usage frequency, and shows their correlations with lAT‐based measures of implicit brand attitudes and brand relationship strength. In Study 2, the contrast between explicit and implicit measures of attitude toward the ad for sportswear advertisements portraying African American (Black) and European American (White) athlete–spokespersons revealed different patterns of responses to explicit and implicit measures in Black and White respondents. These were explained in terms of self‐presentation biases and system justification theory. Overall, the results demonstrate that the IAT enhances our understanding of consumer responses, particularly when consumers are either unable or unwilling to identify the sources of influence on their behaviors or opinions.